Endoscopic transpapillary interventions in the treatment of gallstone disease complicated by obstruction of the terminal Choledochus - Bambyzov, L. M.; Titov, V. S.; Бамбизов, Леонід Михайлович; Тітов, В. С. (НУОЗ ім. П. Л. Шупика, 2022)
The aim of the work is to optimize the existing and develop new methods of endoscopic transpapillary interventions in gallstone disease complicated by obstruction of the terminal choledochus, to reduce the incidence of postoperative complications and mortality.
Ендоскопічні транспапілярні втручання у лікуванні жовчнокам’яної хвороби, ускладненої непрохідністю термінального відділу Холедоха